Maria as Nai Mnuke: Guardian of Land, Body, and Dignity—Reinterpreting Marian Devotion in the Mollo Indigenous Community - Siprianus Soleman Senda; Helidorus F. Anin; Patricius Neonnub; Hendriko Dicky Tae Della; Oswaldus Agusto Haki Mamulak (Wawasan: Jurnal Ilmiah Agama dan Sosial Budaya, 2026)
Marian devotion occupies a central place in Indonesian Catholic spirituality, yet it is frequently understood as an expression of personal piety detached from questions of gender justice and ecological responsibility. This study examines how Marian devotion is reinterpreted within the Mollo indigenous community of East Nusa Tenggara through the concept of Nai Mnuke. This contextual theological construct integrates Catholic Mariology with indigenous relational cosmology. Employing a qualitative approach grounded in reflective ethnography, the study collected data through participant observation, semi-structured interviews, focus group discussions, and document analysis in five villages where Marian devotion and customary practices remain closely intertwined. The findings reveal that Marian devotion functions as a relational religious praxis through which believers cultivate moral agency, communal solidarity, and ecological responsibility. Mollo women emerge as active theological interpreters who negotiate inherited devotional traditions in dialogue with their lived experiences, while Nai Mnuke provides a theological language that connects women’s dignity, care for the land, and Catholic faith within a shared moral horizon. Rather than representing a departure from Catholic orthodoxy, this reinterpretation deepens Marian devotion through creative dialogue between ecclesial tradition and indigenous wisdom. The study contributes to contextual Mariology by integrating Thomistic personalism, contextual feminist hermeneutics, and ecofeminism into a coherent analytical framework for understanding Marian devotion as lived religion. It further demonstrates that contextual Marian devotion can serve as a constructive theological resource for strengthening women’s agency, ecological stewardship, and pastoral engagement within indigenous Catholic communities.